Effects of split-nursing management on growth performance in nursing pigs - T S Donovan; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1996)
We evaluated the effects of split nursing the lightest 50% of pigs per litter or the lightest and heaviest 50% of pigs per litter at birth on growth performance until weaning. We did not observe any effects of split nursing on growth performance in pigs from litter sizes<9 at birth. Additionally, we did not observe a difference in mean ADG or pig weight at weaning. However, we did observe a reduction in the variation of ADG between litters. The resulting decrease in variation leads to approximately a 55% (1.3 vs 3.0) reduction in pigs weighing less than 8 lb at weaning. We conclude that the greatest economic benefits are derived from split nursing the lightest 50% of pigs from litter sizes greater than or equal to 9.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Split nursing; Colostrum; Lactation; Growth